Analisis Tindak Tutur Direktif dalam Percakapan Film “Naga Naga Naga” Yang Disutradarai Oleh Deddy Mizwar : Kajian Pragmatik - Sintita, Tia; Satria, Irwan; Sari, Wenny Aulia (LITERATUR: Jurnal Bahasa, Sastra dan Pengajaran, 2024)
ABSTRACT This research aims to describe the forms and functions of directive speech acts in the conversations of the film "Naga Naga Naga," directed by Deddy Mizwar. The research method used is descriptive. The data source for this research is the dialogues from the film "Naga Naga Naga." Data were collected using the technique of free involvement listening followed by observation, transcription, and note-taking methods. The results indicate that in the dialogues of the film "Naga Naga Naga," six forms of speech acts were identified: commands, requests, invitations, advice, criticism, and prohibitions. Based on the findings, the functions of directive speech acts in the film "Naga Naga Naga" vary. The form of command includes the functions of commanding, instructing, requiring, forcing, and allowing. The form of request includes the functions of begging, offering, and hoping. The form of invitation includes the functions of inviting, encouraging, persuading, supporting, urging, challenging, demanding, and targeting. The form of advice includes the functions of advising, recommending, suggesting, directing, urging, calling, and reminding. The form of criticism includes the functions of reprimanding, insinuating, condemning, and expressing anger. The form of prohibition includes the functions of forbidding and preventing. In conclusion, there are six forms of directive speech acts in the conversations of the film "Naga Naga Naga" by Deddy Mizwar: commands with 28 utterances, requests with 12 utterances, invitations with 21 utterances, advice with 38 utterances, criticism with 27 utterances, and prohibitions with 17 utterances. Keywords: Directive, Film, Speech Act